Atenção visual em crianças com migrânea: um estudo comparativo controlado - Villa, Thaís Rodrigues [UNIFESP] (2011)
Objective: To evaluate the visual attention of children with migraine and compare to the headache free control group. Method: 30 children with migraine, with (n=5) and without aura (n=25), which fulfill the gInternational Headache Society (ICHD-II, 2004) h criteria, 15 female, ages 8 to 12 years and 11 months (average=10.8 }1.5 years), with an average of 5.8 } 3.2 attacks/month, lasting up to 24 hours, and 30 control subjects without headache, 14 female, average age 9,9 }1.3 years. Method of assessment of visual attention: Trail Making Test (TMT) A/B, Letter Cancellation Test, and the computerized test Visual Attention Test . 3rd edition (TAVIS-3) which evaluates reaction time, omission and action errors through subtests of selective (task1), alternate (task2), and sustained attention (task3). Migraine group were evaluated after two days without headache. Exclusion criteria: other systemic diseases, altered neurological examination, psychiatric disorders, learning disorders, epilepsy, head trauma, use of medication (including migraine prophylaxis), and an Intelligence Quotient (IQ) < 80, measured by Wechsler Intelligence Scale 3rd edition. Statistical analysis: Student fs t test and Mann-Whitney fs test, Confidence Interval of 95% (p.0.05). Results: Children with migraine had inferior performance compared to the control group on TMT A (p=0.03) and B (p=0.001), and more action errors on tasks 1 (p=0.032) and 2 (p=0.015) of TAVIS-3, presenting difficulty with selective and alternate attention. Discussion: Attention is a complex neurologic function which depends on structures such as the brain stem, cerebral cortex, and the limbic system and on neurotransmitters such as dopamine and noradrenaline. Conclusion: The neurochemical aspects involved in the physiopathology of migraine and attention mechanisms probably predispose these children to visual attention deficits.